Comparable encryption scheme supporting multiple users in cloud computing. (2018) - Ye, Jun; Miao, Meixia; Chen, Peng; Chen, Xiaofeng
Cloud computing provides a way for secure data sharing, where data should be converted into ciphertext forms before uploading to the cloud servers. At the same time, we need to compare the data on many occasions. Although the privacy is enhanced when data is encrypted, the comparison of encrypted data is inconvenient, especially the data encrypted by different keys. The techniques for secure comparison of ciphertexts are a hot research topic both in the academic research and the industry practice. However, to the best of our knowledge, only a single user's data encrypted by a single key can be compared in the existing schemes. In this paper, we design the first comparable encryption scheme among multiple users, and a novel token transformation technique is provided. In our scheme, different ciphertexts encrypted by different keys can be compared with each other by using our new algorithm and token transformation method. In addition, the security and verifiability characteristics of our scheme guarantee that users can easily verify the comparison result, and the value of the data will not be revealed. Finally, our scheme is flexible, which can be widely used in cloud computing.